96.6k views
3 votes
If f(x) = (x/6) - 5 then use what you know to find f-1(1)

2 Answers

3 votes

Explanation:

SEE THE IMAGE FOR SOLUTION

HOPE IT HELPS

HAVE A GREAT DAY

If f(x) = (x/6) - 5 then use what you know to find f-1(1)-example-1
User Yannik Suhre
by
4.9k points
7 votes

Answer:

f^-1 = 36

Explanation:


f(x) = ((x)/(6) ) -5\\f^(-1) (1) = ?\\f^-^1= \\y = ((x)/(6) ) -5\\ y = (x)/(6)-5\\y+5 = x/6\\Multiply -through- by ; 6\\ 6(y+5) =x\\f^-^1(x) = 6(x+5)\\f^-^1(1) = 6(1+5)\\ = 6(6)\\f^-^1 (1) = 36

User Liam Foley
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.